Epidemiology of overuse injuries among intercollegiate athletes. (1st March 2011) - Yang, J; Cheng, G; Nayar, S; Tibbetts, A; Heiden, E
Abstract : Objective: Research on overuse injuries has been limited among collegiate athletes. This study describes the epidemiology of overuse injuries sustained by Division I intercollegiate athletes. Methods: Injuries were identified using an ongoing injury surveillance system established for Big Ten Athletic Conference universities. A total of 1333 injuries from 21 sports teams at one university during the study period (2005–2008 seasons) were analysed. The injury type, body region and games or practices missed due to the injury were described. Injury rate was calculated as the total number of overuse injuries divided by the total number of athlete-exposures during the same period. Results: A total of 387 overuse injuries (29% of all injuries) were reported during the study period, with 238 (61.5%) for females athletes and 149 (38.5%) for male athletes. The rate of overuse injuries was 18.5 per 10 000 athlete-exposures. Females had a higher overuse injury rate than males, with rate of 24.6 versus 13.3 per 10 000 athlete-exposures. The highest overuse injury rates were observed in women field hockey, softball, women soccer and volleyball, with rates of 70.5, 56.7, 48.3 and 42.6 per 10 000 athlete-exposures, respectively. The most frequent injured body region was lower extremities. The most common injuries were general stress, inflammation and tendinitis. Conclusion: Further analysis is needed to better understand why female athletes are at higher risk of overuse injuries. Effective interventions to prevent and treat these injuries are also warranted.